2010
DOI: 10.1002/bsl.934
|View full text |Cite
|
Sign up to set email alerts
|

Hebephilia: Quintessence of diagnostic pretextuality

Abstract: Hebephilia is an archaic term used to describe adult sexual attraction to adolescents. Prior to the advent of contemporary sexually violent predator laws, the term was not found in any dictionary or formal diagnostic system. Overnight, it is on the fast track toward recognition as a psychiatric condition meriting inclusion in the upcoming fifth edition of the Diagnostic and Statistical Manual of Mental Disorders. This article traces the sudden emergence and popularity of hebephilia to pressure from the legal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…Several courts have found the ''paraphilia NOS, hebephilia'' diagnosis used in civil commitment proceedings to be either not demonstrably a mental disorder at all or not a serious enough mental disorder to meet the threshold for application to the sexual predator civil hearings (Franklin 2010a). The attempt to place this disorder in the DSM is partly an attempt to legitimize this diagnosis and neutralize such objections.…”
Section: Dsm-5 Proposed Diagnostic Criteria For Pedohebephiliamentioning
confidence: 98%
“…Several courts have found the ''paraphilia NOS, hebephilia'' diagnosis used in civil commitment proceedings to be either not demonstrably a mental disorder at all or not a serious enough mental disorder to meet the threshold for application to the sexual predator civil hearings (Franklin 2010a). The attempt to place this disorder in the DSM is partly an attempt to legitimize this diagnosis and neutralize such objections.…”
Section: Dsm-5 Proposed Diagnostic Criteria For Pedohebephiliamentioning
confidence: 98%
“…"Hebephilia" was suggested for inclusion in the DSM-5 (Blanchard et al 2009 ). Although the validity and usefulness of this category has been repeatedly criticized (Franklin 2010 ; Wakefi eld 2011 ; Singy forthcoming ), and although the category was ultimately rejected by the APA's Board of Trustees, "hebephilia" is nevertheless regularly invoked in the courtroom. Today, like in the nineteenth century, the paraphilias are born in the courtroom, not on the couch.…”
Section: Forensic Psychiatry Without the Dsm And Vice Versamentioning
confidence: 96%
“…They may also, unfortunately, be useful in a consequential (Sreenivasan, Frances, & Weinberger, 2010) or pretextual sense (Franklin, 2010) for buttressing inaccurate sex offender risk assessment opinions.…”
Section: Examplementioning
confidence: 96%
“…Psychologist Karen Franklin (2010), in particular, has inventoried these criticisms and concluded that "expanding the definition of pedophilia -a diagnosis with already poor interrater reliability -into a broader definition of pedohebephilia has the potential to dramatically increase the scope and power of the sex offender civil commitment industry" in a way that "will invite . .…”
Section: Introductionmentioning
confidence: 97%